If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(3z + -7) = 33 Reorder the terms: -6(-7 + 3z) = 33 (-7 * -6 + 3z * -6) = 33 (42 + -18z) = 33 Solving 42 + -18z = 33 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -18z = 33 + -42 Combine like terms: 42 + -42 = 0 0 + -18z = 33 + -42 -18z = 33 + -42 Combine like terms: 33 + -42 = -9 -18z = -9 Divide each side by '-18'. z = 0.5 Simplifying z = 0.5
| 36-(3x+4)=2(x+4)+x | | x-5x+4x-7x= | | x^3-5x^2+2x=-1 | | 3+2k=17 | | x=7ln(y^2-48) | | 2w^2+7w=0 | | 7x=19(2x-7) | | -2x-x+1=0 | | 0.2x^5-2x^3+1.8x+5=0 | | 7+12p=-5 | | -2x-6=2-4-(x-1) | | 0.2x^5-2x^3+1.8x+2=0 | | R^2+10r-30=0 | | 3a+23=53 | | 4x^3+22x^2+24x=0 | | 2x^2-sinx+1=0 | | 16x^2-54x-16=0 | | 1-6x-3x=-17 | | (15)(13)+(15)(7)= | | 2a-18=34 | | 2x-sinx+1=0 | | 8n+2+5n=19 | | 4y+10=x | | 2x=-2-y | | 13=x(4-x) | | 45+0.25m=70+0.15m | | 2f+18=14 | | 2x+y-2z=14 | | V-4v+9=b-12 | | 3z+(-2)=8 | | 35-8r=-r+3(-3+5r) | | 5(2-x)-3(4-2x)=12 |